La sculpture celtique anthropomorphe à Châteaumeillant (Cher) : découverte récente d’une main en grès - Sophie Krausz (Revue Archéologique du Centre de la France)
During the 2007 excavation, three fragments of an anthropomorphic sandstone statue were found at the oppidum at Châteaumeillant. The most noteworthy element is a half-scale hand. This material seems to have been discarded as rubbish in a pit otherwise containing a homogeneous assemblage of sherds attributable to the beginning of La Tène D1a. The hand is sculpted in the round and therefore cannot have come from an example of the usual series of sculptures found in Berry, in which the lower arms are placed in front of the chest. It is probably from a figure sitting cross-legged, of which several examples are known in central France. Although usually recovered from Gallo-Roman contexts, such statues are clearly in a Gallic tradition. The recovery of these fragments mixed with rubbish in a pit, leads us to speculate on the events which preceded their deposition. Given the context in which the fragments were found, their breakage may seem simply have been accidental, but this article reviews evidence for the severing of hands which, like that of heads, is a component of the Celtic warrior tradition.